Design and hardware construction of series-parallel resonant DC-DC converter / Rahmah Adnan - Adnan, Rahmah (2009)
With the rapid growth of microelectronic technology, high performances of Integrated Circuits (ICs) bring huge challenge to design the power supplies. Fast loop response is required to handle the high transient current of devices [1]. Nowadays, the smaller sizes of power components is demanded in order to reduce the size of integrated circuits. The best way to meet these harsh requirements is by increasing the switching frequency of the power supplies [1]. But, by increasing the switching frequency the switching loss and gate charge loss will increase proportionally. Therefore, the resonant switching or soft switching was introduced in order to minimize and mitigate these problems. This thesis describes the topology of resonant converter which is to minimize the switching losses. This project focuses to analyze the topology of Series-Parallel Resonant DC-DC Converter (SPRC). The main objective of this project is to design and construct the prototype of Series-Parallel Resonant Converter (SPRC) to provide 9V, 0.45A output for 10 kHz application. The advantages and disadvantages of these resonant converter and SPRC are presented. The details methods of designing the gate driver and SPRC are provided. The thesis also includes the results obtained from PSIM simulation and experimentation.